Optimasi Pengelolaan Tong Sampah Cerdas Melalui Pendampingan Teknis Di Desa Cibuntu Kuningan - Agus Bahtiar; Edi Wahyudin; Garzitta Aditya Fahreza; Azizah Nuraini Hardadi; Auldi Dwi Cahyani Kusumawardani (CV. Multi Kreasi Media, 2023)
Cibuntu Village, Kuningan, is the partner location that is the focus of this project. A case that often occurs in Cibuntu Village is the accumulation of waste that is not managed properly. This rubbish is thrown anywhere, causing environmental pollution, attracting nuisance animals, and harming the health of local people. Some areas are often flooded due to blockage of drainage channels by rubbish. Automatic trash cans are a technological innovation that aims to facilitate and increase efficiency in waste management. By using sensors and automatic mechanisms, this trash can can detect and classify types of waste independently. Automatic trash cans can be part of a smart city concept that uses technology to improve the quality of life of residents.